Synthesis and biological evaluation of novel A-seco-taxoids derived from 1-deoxybaccatin VI. Issue 2 (17th January 2018) - Qiu, Wei-Qing; Cui, Yong-Mei; Tang, Ping; Qiu, Yuan-You; Lin, Hai-Xia
Abstract: Three novel nor-seco-taxoids13, 15, 23 in which the A rings are cleaved but the B, C, and D rings are retained were prepared from 1-deoxybaccatin VI via its nor-dioxo derivative and their structures were confirmed by 1 H NMR, 13 C NMR and high resolution MS. Oxidative introduction of C-1 hydroxyl to 1-deoxybaccatin VI with oxidising agent KBrO3 and catalyst RuCl3 led to the dioxo derivative6 and its structure is determined by X-ray crystallographic analysis. A-seco taxoids13, 15, 23 with a C-13 ester linkage were tested for cytotoxic activity and all compounds showed no measurable cytotoxic activity against HCT-116 cell line. However, 1-deoxy-9a-dihydrotaxane analogue4 semi-synthesised from 1-deoxybaccatin VI is 10-fold less cytotoxic than paclitaxel, indicating the indispensible nature of the A ring double bond for the bioactivity of paclitaxel. Abstract :